Electroacupuncture combined with trigonelline inhibits pyroptosis in cerebral ischemia-reperfusion by suppressing autophagy via the PI3K/AKT/mTOR signaling pathway - Zhengguo Qiu; Jianbing Ma; Xiaqing Zhang; Mingna Jiao; Liqiang Zhi (Brain Research Bulletin)
Background: Electroacupuncture (EA) and trigonelline (TG) have been reported to be beneficial in alleviating cerebral ischemia/reperfusion injury (CIRI). However, the synergistic effects of EA and TG in CIRI and the underlying mechanism have not been demonstrated. Methods: Rats were subjected to middle cerebral artery occlusion (MCAO) surgery and reperfusion (MCAO/R) to establish a CIRI model. Neurological deficit score was evaluated using Garcia’s scale. Cerebral infarction in rats was determined using TTC staining. Brain tissue morphology was assessed by HE staining. The expression of various proteins was measured using IF assay and western blot. Results: EA or TG treatment could effectively ameliorate neurological disorders, attenuate cerebral infarction and reduce neuronal damage in brain tissue in CIRI rats. In addition, EA or TG treatment suppressed autophagy and pyroptosis in CIRI rats. More importantly, synergistic effects of EA and TG intervention in CIRI rats were observed in ameliorating neuronal damage and suppressing autophagy and pyroptosis, while Rapa, an inducer of autophagy, strengthened these effects in MCAO/R-induced rats. Furthermore. Rapa reversed EA in combination with TG-mediated improvement of neuronal damage and suppression of autophagy and pyroptosis in CIRI rats. Notably, the PI3K/AKT/mTOR pathway was inactivated in CIRI rats and EA combined with TG enhanced the activation of the PI3K/AKT/mTOR pathway. LY294002, an inhibitor of the PI3K/AKT/mTOR pathway, stimulated autophagy and pyroptosis in CIRI rats and reversed EA combined with TG-mediated suppression of autophagy and pyroptosis. Conclusion: EA combined with TG suppressed pyroptosis, which was dependent on inhibition of autophagy in CIRI rats through activation of the PI3K/AKT/mTOR signaling pathway.